2023
DOI: 10.1021/acsami.2c18685
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization Short-Circuiting with Weak Electrolytes Erodes the Efficiency of Bipolar Membranes

Abstract: Bipolar membranes (BPMs) are critical components of a variety of electrochemical energy technologies. Many electrochemical applications require the use of buffers to maintain stable, nonextreme pH environments, yet the impact of buffers or weak acids/bases on the electrochemical behavior of BPMs remains poorly understood. Our data for a cell containing weak electrolytes is consistent with internal pH gradients within the anion exchange membrane (AEM) or cation exchange membrane (CEM) component of the BPM that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 61 publications
2
14
0
Order By: Relevance
“…The open-circuit Vmem values for catholytes containing 1 M KOH, 0.75 M KOH + 0.25 M KOAc and 0.25 M KOH + 0.75 M KOAc were found to be close to −59 mV•ΔpH (where ΔpH = pHcatholyte − pHanolyte) or, equivalently, −59 mV•pKa(H2O), whereas that for the catholyte containing 1 M KOAc was close to −59 mV•pKa (AcOH) (Figure 2(a)). The pKapinned open-circuit Vmem value, or VpKa, for the latter case is consistent with our findings in our previous study, 38 in which we showed that ionic short-circuiting processes led to buffering of the bipolar interface by the acid-base couple present (H2O/OH − and AcOH/OAc − , respectively). In the case of 1 M H2SO4 | 0.75 M KOH + 0.25 M KOAc and 1 M H2SO4 | 0.25 M KOH + 0.75 M KOAc, the presence of OH − ensures a high pH in the region of the AEM close to the bipolar interface, resulting in the open-circuit Vmem being dominated by the H + /OH − recombination couple and pinned to ca.…”
Section: Mechanistic Investigation Of Forward Bias Polarization In Mi...supporting
confidence: 93%
See 3 more Smart Citations
“…The open-circuit Vmem values for catholytes containing 1 M KOH, 0.75 M KOH + 0.25 M KOAc and 0.25 M KOH + 0.75 M KOAc were found to be close to −59 mV•ΔpH (where ΔpH = pHcatholyte − pHanolyte) or, equivalently, −59 mV•pKa(H2O), whereas that for the catholyte containing 1 M KOAc was close to −59 mV•pKa (AcOH) (Figure 2(a)). The pKapinned open-circuit Vmem value, or VpKa, for the latter case is consistent with our findings in our previous study, 38 in which we showed that ionic short-circuiting processes led to buffering of the bipolar interface by the acid-base couple present (H2O/OH − and AcOH/OAc − , respectively). In the case of 1 M H2SO4 | 0.75 M KOH + 0.25 M KOAc and 1 M H2SO4 | 0.25 M KOH + 0.75 M KOAc, the presence of OH − ensures a high pH in the region of the AEM close to the bipolar interface, resulting in the open-circuit Vmem being dominated by the H + /OH − recombination couple and pinned to ca.…”
Section: Mechanistic Investigation Of Forward Bias Polarization In Mi...supporting
confidence: 93%
“…When an analogous series of cells of the type x M H2SO4 + y M NH4Cl | 1 M KOH (x + y = 1) were polarized in forward bias (Figure S4), we observed identical behavior to the 1 M H2SO4 | x M KOH + y M KOAc cells. Additionally, consistent with previous experimental 38,39 and computational 33 reports, we observe that the presence of polyprotic buffer species in the cell 1 M H2SO4 | 1 M KxHyPO4 (x + y = 3), gave multiple limiting current plateaus with inflection points coinciding with ca. −59 mV•pKa (H3PO4) (−130 mV), ca.…”
Section: Mechanistic Investigation Of Forward Bias Polarization In Mi...supporting
confidence: 91%
See 2 more Smart Citations
“…27,56 The 1 M KHCO3 case, however, is more intriguing. While previous studies have suggested that the low applied potential current onset for BPMs in weak buffer electrolytes is entirely driven by titration currents resulting from dissociation of the weak acid buffer (i.e., the HCO3 -anion in this case) in the CL, 27,49,57 the model suggests that current density in the initial linear feature is still primarily dominated by field-enhanced water dissociation. Field-enhanced dissociation of the buffering anion accounts for up to 50% of the observed current density.…”
Section: Agreement With Experiments and Breakdown Of Partial Current ...mentioning
confidence: 66%